Post-partum acute kidney injury: sorting placental and non-placental thrombotic microangiopathies using the trajectory of biomarkers. Issue 9 (25th February 2019) - Meibody, Fleuria; Jamme, Matthieu; Tsatsaris, Vassilis; Provot, François; Lambert, Jérôme; Frémeaux-Bacchi, Véronique; Ducloy-Bouthors, Anne-Sophie; Jourdain, Mercédès; Delmas, Yahsou; Perez, Pierre; Darmian, Julien; Wynckel, Alain; et al.
Abstract: Background: Among the severe complications of preeclampsia (PE), acute kidney injury (AKI) is problematic if features of thrombotic microangiopathy (TMA) are present. Although a haemolysis enzyme liver low-platelets syndrome is considerably more frequent, it is vital to rule out a flare of atypical haemolytic and uraemic syndrome (aHUS). Our objective was to improve differential diagnosis procedures in post-partum AKI. Methods: A total of 105 cases of post-partum AKI, admitted to nine different regional French intensive care units from 2011 to 2015, were analysed. Analysis included initial and final diagnosis, renal features, haemostasis and TMA parameters, with particular focus on the dynamics of each component within the first days following delivery. A classification and regression tree (CART) was used to construct a diagnostic algorithm. Results: AKI was attributed to severe PE ( n  = 40), post-partum haemorrhage ( n  = 33, including 13 renal cortical necrosis) and 'primary' TMA ( n  = 14, including 10 aHUS and 4 thrombotic thrombocytopenic purpura). Congruence between initial and final diagnosis was low (63%). The dynamics of haemoglobin, haptoglobin and liver enzymes were poorly discriminant. In contrast, the dynamic pattern of platelets was statistically different between primary TMA-related AKI and other groups. CART analysis independently highlighted the usefulness of platelet trajectory in the diagnostic algorithm. Limitations of this study include that only the most severe cases were included in this retrospective study, and the circumstantial complexity is high. Conclusion: Trajectory of platelet count between admission and Day 3 helps to guide therapeutic decisions in cases of TMA-associated post-partum AKI. Our study also strongly suggests that during the post-partum period, there may be a risk of transient, slowly recovering TMA in cases of severe endothelial injury in women without a genetic mutation known to induce aHUS.